Comparative study between PI and SMC controllers for DFIG using fuzzy wind power estimator - Atef Jemmali; Khaled Elleuch; Hafedh Abid; Ahmed Toumi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
In this paper, we are interested in the control of the rotor current of the doubly feed induction generator (DFIG), that is used in wind turbines. In this context, we present a comparative study between two types of controllers. The first is based on a classic PI proportional-integral control, while the second is based on the SMC sliding control. The command chain uses a fuzzy estimator of the wind power, which makes it possible to determine the reference speed of DFIG. The system includes essentially a turbine, two converters, one on the rotor side and the other on the grid side, and a filter. The grid-side converter is used to maintain a constant DC bus voltage and to control rotor reactive power. The rotor side converter is used to control the speed of the DFIG to guarantee maximum power extracted from the turbine. In addition, this converter allows controlling the reactive power through the control of the rotor current according to the axis "d" of the frame linked to the rotating field. The simulation results show the effectiveness of sliding mode control (SMC) for the considered system.